Threshold effect of green credit on firms' green technology innovation: Is environmental information disclosure important?. (20th December 2022) - Su, Xin; Pan, Chao; Zhou, Shengshi; Zhong, Xi
Abstract: In order to cope with the threat of climate warming, countries worldwide have taken many measures. Supporting green and low-carbon development through financial means is one of the crucial measures. Banks dominate China's financial system, and green credit has become the leading force in China's green financial system. Facing the increasingly tricky environmental situation, how to achieve the firms' sustainable development with the help of green credit has become a research hotspot. We used the green patent data of 549 listed Chinese A-share firms from 2012 to 2019 to empirically test the nonlinear impact of green credit on firms' green technology innovation from the perspective of corporate environmental information disclosure. The study found that: (1) firms' green technology innovation will be inhibited if the green credit is lower than the threshold value. Otherwise, it has no impact on firms' green technology innovation. (2) Corporate environmental information disclosure has a significant threshold effect on the relationship between green credit and green technology innovation. High-level information disclosure constitutes an essential element for green credit to promote firms' green innovation, which can effectively alleviate the inhibitory effect of green credit. (3) Finally, the mitigation effect of environmental information disclosure was significant only in non-heavy polluting and state-owned firms. Our research contributes to a more comprehensive understanding of the logical relationship between green credit and firms' green technology innovation, verifies the critical role of environmental information disclosure in it, and provides inclusive and reliable practical evidence for improving green credit systems in various countries and firms' green and low-carbon development.